PEMBERIAN AIR SISTEM IRIGASI TETES DAN KONSENTRASI PUPUK PELENGKAP CAIR (PPC) PADA PERTUMBUHAN DAN HASIL TANAMAN CABAI (Capsicum annuum L.) - Henri D Simaremare; Adiwirman '; Ardian ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to determine the effect of the interaction of water supply, drip irrigation systems and complementary liquid fertilizer concentration is right to promote the growth and production of the red pepper plant. The completely randomized design (CRD) was used with 2 factors and 3 replications. The Honestly Significant Different test (HSD) at the 5 % level was used for means separation. The first factor is the provision of water consisting of A1 = Volume of water 2,400 ml; A2 = Volume of water 1,800 ml; A3 = volume of water 1,200 ml of water. The second factor is the complementary liquid fertilizer comprising P0 = 0 cc/l of water; P1 = 2 cc/l of water; P2 = 4 cc/l of water. Correlation test used fordetermining the relationship between all variables. Results showed that both treatments gave significant effect on the variable crown width and weight of the fruit crop but not on th significant on plant height, height of dichotomous, stem diameter, flowering age, harvesting age, length of fruit, fruit diameter and weight per fruit. The provision of water 2400 ml /plant/day and a complementary liquid fertilizer 2 cc/l of water can promote the growth of the canopy width and the provision of water 2400 ml/day/plant and complementary liquid fertilizer 4 cc/l of water can increase the weight of the fruit crop. The main influence water supply does not affect significantly affected all variables observation. The main influence of complementary liquid fertilizer 4 cc/l water significantly affects the variable fruit weight per plant. Keywords: Drip irrigation, fertilizer liquid complements, red chili